Celebraciones belgranianas: política y género en la fiesta patria (2012-2021) - Pablo Ortemberg; Mariana Caminotti (Caravelle)
This article discusses the Belgranian celebrations through the politicization of gender policies in Argentina. These celebrations reflect a gradual visibility of women and LGBTIQ groups. These actions become a public arena to redefine a national identitarian “nosotrxs”, including several meanings and multiple resistances. They can partly be considered as a reaction towards demands of gender equality, but also as deriving from the specific nature of patriotic celebrations.